A case–control study of occupational contact levels in the childhood leukaemia cluster at Seascale, Cumbria, UK. Issue 8 (4th August 2015) - Kinlen, Leo J
Abstract : Objectives: To investigate adult occupational contact levels and risk of childhood leukaemia and non-Hodgkin's lymphoma (LNHL) in Seascale, an association found in other situations of rural population mixing (PM). Design: Matched case–control study. Setting: Seascale, Cumbria, UK. Participants: For each case of LNHL recorded in patients under age 25 years during 1950–2006, up to 20 matched controls were chosen and parental occupational details obtained; an exception was a single working young adult, whose own occupation (and that of controls) was used. Primary outcome measures: Contact levels of occupations were categorised as: low/medium (reference group), high or very high contact levels, as in previous studies, with provision for certain unusual occupations. In particular, specialist policemen responsible for security and access at the nearby Sellafield nuclear complex were allocated to the highest contact category, and those Sellafield employees who worked in controlled areas to the middle (high) category. Since of possible bias, unusual contact aspects noted in the main research and development (R&D) building were reserved for a supplementary analysis. ORs were calculated for the occupational contact levels. Results: Compared to the reference group, the social class adjusted ORs for the high and very high contact categories were 8.18 (95% CI 0.95 to 70.33) and 14.90 (1.20 to 184.90), respectively, with a significant trend across the categories (p value=0.024). In the supplementary analysis with R&D workers moved to the very high contact category, the OR for the latter became 29.68 (2.12 to 415.79), and the p value for trend, 0.011. Conclusions: The Seascale LNHL excess was most marked among those young people linked with high occupational contact levels; it is therefore not an exception to the pattern of family infection shown by other PM-related excesses. The findings have implications for the choice of controls in certain types of virus study.